#TITLE_ALTERNATIVE# - DADAN DAMAYANDRI SYAEFUL MILLAH SAPUTRA (NIM : 12207048),
Well testing is important to do for knowing the characteristic of formation (reservoir) and for calculate optimum flow rate (optimization) from the well. By determining the right well opening time for well test like back pressure test, formation charcteristics that can be analyzed will be more accurates. The well opening time correlation that were present such as Asmoro SantoÃ‚Â„s correlation can be used for back pressure test and then the correlation is developed and validated by using Drill Stem Test (DST) data from 20 wells with different formation fluids and formations characteristics. From this correlation‟s validation, we can know the constraints of the assumption from the correlation and will increase the accuration rate of the correlation. Reservoir simulation is used to generate a profil of pressure vs time of the back pressure test. Optimum oil flow rate can be known from nodal analysis that uses Inflow Performance Relationship (IPR) and Tubing Performance Relationship (TPR) from the well. And then, optimum flow rate is developed by using the parameter sensitivity analysis from IPR and TPR that are known. The result‟s then is compared with Asmoro‟s optimum oil flow rate correlation. The result, the new generated correlation have accuration rate that is better than the previous correlation.